Antisipasi Keterlambatan Proyek Pembangunan Shelter dengan Menggunakan Metode What-If Analysis - Ineu Widaningsih; Anastasia Lidya Maukar; Avania Shinta (JIE Scientific Journal on Research and Application of Industrial System, 2018)
The purpose of this study is to identify the delay in building shelter projects and activities that cause delays. This research will provide suggestions on steps to be taken to overcome delays. This research uses two methods of control, namely the "what-if analysis" method for solutions if there is a delay in the project, as well as a method of shortening the duration of critical paths Duration Crashing on critical infrastructure with the addition of workers or the application of overtime work as an alternative control were performed. Currently, the critical path has not been identified and there is no solution provided to overcome the problem of delays in shelter construction projects. The target duration of the construction of the shelter construction project is known for 14 days but it has been delayed into 35 days. The results of this study are findings of some critical activities that can cause delays and what-if analysis is done for time acceleration of 10% to 100%.Keywords: What If analysis, Critical Path Method, shelter, Duration Crashing.